India NPS Seminar Series: Water & Energy Policies for Transforming Agri-Food Systems - Oct 2022 (Blog) - CGIAR (CGIAR System Organization, 2023)
A joint session was organized by IWMI, IFPRI, and NPS on “Water & Energy Policies for Transforming Agri-Food Systems in Odisha as part of the Policy Roundtable in October 2022. The state has done a spectacular job in electrifying irrigation pumps by making certain changes in policies such as cross subsidizing unit rates to use energy, dug-well based solar water pumps so as to increase irrigation potential and cropping intensity within the state. Despite these efforts, 16 out of 30 districts in Odisha are severely irrigation-deprived and still the agricultural income of the farmers in the state turns out to be one of the lowest. The session focus was to discuss on improving access to irrigation through grid or solar power, challenges faced in Grid connected systems, and accelerating adoption of Micro Irrigation Systems. The suggestions from the session were: – a). There needs to be more convergence within the department schemes. In order to scale up the adoption of MI systems, solar pumps and utilize the irrigation surplus, it is required to have more convergence within various schemes, so as to identify the target beneficiaries and improve the scale of adoption of these schemes. b) Building auxiliary structures along the canal systems such as pond-based systems. c) To promote solar pumps/solar irrigation, it is necessary to identify innovative financial & institutional models which are successful in the states, promoted by the government agencies, NGOs & private partners. d) Rental models for promotion of solar schemes and also models for utilizing energy in both farm and non-farm activities. e) Creating Awareness among farmers on schemes and innovative models through capacity building activities.